Process Standardization of Ready-to-eat Pasteurized Crab spread from Marine Blue Swimming Crab (Portunus pelagicus) Incorporated with Threadfin Bream Surimi - Jiso Thomas, Seba T.; Archana, G.; Abhilash, S.; Sabu, S.; Sunooj, K. V.; Gopal, T. K. S. (Fishery Technology, 2020)
Ready-to-eat pasteurized crab spread was standardized from blue swimming crab (Portunus pelagicus) and surimi from threadfin bream (Nemipterus japonicus). Spread was prepared incorporating crab meat and surimi in 1:1 ratio, vacuum packed in monolayer retortable polypropylene pouches with screw cap and pasteurized to core temperatures 86oC[T1] and 89oC[T2] for a total processing time of 90 min and 50 min, respectively. Both the spreads were subjected to proximate, organoleptic and microbial analysis for the assessment of shelf life under chilled condition (3oC) for six months. The pH values of T1 and T2 reduced during the storage period (p